1991
DOI: 10.1007/bf02657691
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperoxide formation in soybean seeds during storage

Abstract: Forrest' soybeans were stored for two years, and the extracted lipids were assayed for hydroperoxide content. The crude lipid was separated by high-performance liquid chromatography {HPLC), and three hydroperoxide peaks plus the triglyceride peak were measured every two months. There was a lag in hydroperoxide production for the first nine months followed by a steady increase for the remaining twenty-two months. This method of measuring changes in lipid oxidation should be useful for monitoring seed changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 6 publications
2
13
0
1
Order By: Relevance
“…1) and an increase in the mean germination time, which is an indication of declining seed vigour (Tab. This loss of germinability has been attributed to the oxidative damage caused during ageing (Haider et al 1983, Gidrol et al 1989, Bailly et al 1996, De Paula et al 1996, which is consistent with the results found for seeds of other species (Buchvarov and Gantcheff 1984, Hailstones and Smith 1988, Clark and Snyder 1991, Sung and Jeng 1994, Sung 1996. A similar effect was observed in aged or deteriorated sunflower seeds (Gidrol et al 1989, Bailly et al 1996, De Paula et al 1996.…”
Section: Discussionsupporting
confidence: 84%
“…1) and an increase in the mean germination time, which is an indication of declining seed vigour (Tab. This loss of germinability has been attributed to the oxidative damage caused during ageing (Haider et al 1983, Gidrol et al 1989, Bailly et al 1996, De Paula et al 1996, which is consistent with the results found for seeds of other species (Buchvarov and Gantcheff 1984, Hailstones and Smith 1988, Clark and Snyder 1991, Sung and Jeng 1994, Sung 1996. A similar effect was observed in aged or deteriorated sunflower seeds (Gidrol et al 1989, Bailly et al 1996, De Paula et al 1996.…”
Section: Discussionsupporting
confidence: 84%
“…1988), although a series of other deteriorative changes such as damage to proteins and nucleic acids occurs (reviewed by McDonald 1999). Modification of membrane composition and function affects seed quality by decreasing seed germination and normal development (Wilson and McDonald 1986, Halistones and Smith 1988, Pukacka and Kuppier 1988, Clark and Synder 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of lipoxygenase and oxygen, unsaturated fatty acids form peroxides . Through the action of hydroperoxide lyase, these lead to the formation of hexanal isomers and the low molecular mass acids that are responsible for rancidity . The most intense bitter taste and the astringency observed in tofu made from aged soybean are related to the conversion of isoflavone glucosides to aglycones.…”
Section: Resultsmentioning
confidence: 99%